The Struggle to Decommodify the Service Sector: The Canadian Auto Workers and the Casino Industry - Mazar, Alissa (Relations industrielles / Industrial Relations, 2019)
Research objective: Through relatively higher unionization rates within the casino industry, casino employment provides a counterexample to the connection between low-skill service work and low wages. The existing literature, however, suggests that casino workers embrace a commodified vision of their labour. It is of interest to understand whether and how unions are successful in decommodifying both ideologically and materially, wage entitlements in this expanding industry as this is a main mechanism through which unions challenge income inequality. This article examines the Canadian Auto Workers’ (CAW) attempt to decommodify wages in the casino industry.Methodology: These findings are based on a case study of Casino Windsor, located in Windsor, Ontario—the automotive capital of Canada and the first city to host a resort casino outside of Atlantic City and Las Vegas. Ninety-one interviews were conducted with Windsor stakeholders (20), and automotive (43) and casino (28) workers. The local newspaper from 1994-2014 is also examined and descriptive statistics are utilized.Results: Casino workers initially did adopt a decommodified vision of wage entitlements; yet, due to political—the New Democratic Party of Ontario—and institutional—low sectoral union density—forces, casino workers during 2014-2015 interviews embrace a service mind where wages are determined by a market-oriented human capital model.Conclusions: CAW union representatives and the casino membership now view the CAW’s attempt to bring an industrial mindset into the casino as a mistake, naturalizing the link between decommodified wages in automotive manufacturing and the market-oriented wage entitlements of the service sector. This case study marks a critical lost opportunity by the CAW to decommodify wage entitlements in the casino industry and the broader service sector.